Menstrual Cycle Irregularities a Reproductive Signal of Thyroid Dysfunction - Jabeen, Mussarat; Zuhra, Hina; Heema, Heema; Rauf, Isma; Samreen Hamid, Beenish; Rehman Hashmi, Shaista (Journal of Neonatal Surgery, 2025)
Background: Thyroid hormones play an important role in physiological activities of reproduction in women. Even the slightest disturbances with the thyroid activity can alter the normalcy of the menstrual cycle, ovulation and endometrial stability. Mostly in this way, menstrual complaints are the first clinical manifestations of a latent thyroid disorder particularly in the women of reproductive age. Objective: To determine the frequency of menstrual cycle irregularities among women with thyroid dysfunction and to assess the association between thyroid status and different menstrual patterns. Methodology: It was an observational study carried out in the Liaquat Memorial Hospital, Kohat, between 1st January 2025 to 30th June 2025. Seventy two-two women between the ages of 15 to 45 years who reported with menstrual complaints were enrolled. The detailed menstrual and reproductive history was interviewed and clinical examination and thyroid functioning tests were performed: serum TSH, free T4, and thyroid peroxidase antibodies. The participants were categorized based on thyroid condition and their menstrual cycles were compared. Appropriate tests were used to carry out statistical analysis where a p-value of less than 0.05 was considered statistically significant. Results: Of the 72 participants, thyroid dysfunction was noted in 44 (61.1%). Women who were hypothyroid and hyperthyroid had significantly increased incidence of menstrual irregularities compared to euthyroid individuals (p = 0.001). The most prevalent abnormalities observed in the menstrual cycle are oligomenorrhea, menorrhagia and amenorrhea. The positivity of thyroid peroxidase antibody was more among women having irregular cycles. Conclusion: Thyroid dysfunction, particularly hypothyroidism, is strongly associated with menstrual cycle irregularities. Routine evaluation of thyroid function in women presenting with abnormal menstrual patterns may allow early diagnosis and timely management, thereby improving reproductive health outcomes..